Presença do ideário neoliberal nos sentidos e significados sobre trabalho em estudante da educação de jovens e adultos: uma análise sócio-histórica - D'Oliveira, Érika Pessanha (2007)
This work intended to apprehend the presence of the neoliberal ideology in the sense and meanings of labour in a 3rd year high-school student of the Youngster and Adult Educational Program (EJA). This moment of the educational process was chosen as a methodological resource. The theoretical perspective used in the research understands the EJA student according to the Socio-Historical Psychology principles, whose system of methodological and epistemological references sees man as built through social productions relations. The economy globalization along with the conditions of work progressively more flexible and precarious leverages the diffusion of the neoliberal ideology. To this research, countersigned by the qualitative approach, a group with ten students with that profile was formed in a state public school in São Paulo, and then the research subject was chosen. During the group session, the choice of the subject was based in the following criteria: involvement with the theme, absorption and pertinence, and personal availableness. Once the only subject was established, two half-structured interviews were made to investigate her professional and personal life, with the purpose of uncovering the senses and meanings of labour to the subject.The analysis procedure occurred through the agglutination of pre-indicators, later organized in indicators. Once articulated and systematized these indicators showed three signification nucleus. The organized nucleus were: The labour world and consumption and life project , Personal efforts today and forever , World vision and television mass media . The scenery of maintenance of the neoliberal ideology guides the ways of insertion of men in the world of labour, in such a way that it was possible to identify, in the student speech, the personal effort as key to the success and an emphasis on the individuality encapsulated in the family cell. Besides that, the television mass media constituted the responsible for knowledge transmission, and school education as the space of care and reassertion of family values; aspects which affects her ways to criticise, feel and act in the world. Thus, as a conclusion, it is possible to say that the ideology, and, more specifically as one of its elements, the personal effort notion, constitutes a decisive element, marking the process of insertion of the student in the labour world as something ideological, deprived of a process of appropriation of its constitutive mediations